'Evolutions' and 'revolutions' in manufacturers' implementation of industry 4.0: a literature review, a multiple case study, and a conceptual framework. Issue 3 (17th February 2021) - Calabrese, Armando; Levialdi Ghiron, Nathan; Tiburzi, Luigi
Abstract: This study addresses Industry 4.0 from a managerial perspective. A systematic literature review is used to identify the Industry 4.0 enabling technologies, strengths, weaknesses, opportunities, and threats, i.e. its 'E-SWOT' elements. Then, these elements are analysed interviewing the managers of 39 companies of different sizes, industrial sectors, and service levels. The results show that there are differences in the adoption rates of the enabling technologies depending on the size of the firms, across the four industrial sectors represented. On the other hand, no difference in the adoption rates has been observed among manufacturers with different service levels. The managers view Industry 4.0 as a bundle of technologies facilitating end-to-end industrial process monitoring, and fail to perceive the prospects of developing value-added solutions for their customers. Furthermore, managers are worried that the wave of '4.0 innovation' could enable big and 'savvy' tech companies to enter their market and threaten their survival. Based on these results, the research argues that Industry 4.0 represents an 'evolution' in factory operations and a potential 'revolution' in the manufacturers' value proposition, and concludes that most manufacturers have so far failed to seise the Industry's 4.0 revolutionary opportunities.